Analisis Stres Karyawan Bekerja Di Gerai Makanan Cepat Saji Pada Saat Dan Pasca Pandemi - Andini, Rizki Dwi; Zainun, Zainun (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
This study aims to determine employee stres in the workplace of fast food outlets during and after the pandemic. The type of research used is descriptive qualitative. The instruments used are a list of questions and notes, electronic devices such as gadgets, cameras for recording during interviews. The informants consisted of 5 informants. The research location is at Reechees Factory, Setia Budi branch while data was collected through observation, interviews and documentation. The results of research on employee stres during the pandemic reduced customers coming to outlets, decreased sales or targets, employee shortages or layoffs, being careful, not full work in a month. After the pandemic, employees often experience increased customer stres, causing frequent overtime work that exceeds 40 hours per week, and lasts for at least three consecutive weeks.